2009
DOI: 10.1212/01.wnl.0000340983.00152.69
|View full text |Cite
|
Sign up to set email alerts
|

Yield of combined perfusion and diffusion MR imaging in hemispheric TIA

Abstract: Objective: Transient ischemic attacks (TIA) predict future stroke. However, there are no sensitive and specific diagnostic criteria for TIA and interobserver agreement regarding the diagnosis is poor. Diffusion-weighted MRI (DWI) demonstrates acute ischemic lesions in approximately 30% of TIA patients; the yield of perfusion-weighted MRI (PWI) is unclear. Methods:We prospectively performed both DWI and PWI within 48 hours of symptom onset in consecutive patients admitted with suspected hemispheric TIAs of Ͻ24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
84
3
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(99 citation statements)
references
References 26 publications
11
84
3
1
Order By: Relevance
“…With respect to the timing of patient assessment after the index event, in 10 studies TIA patients were assessed within 24 hours of symptoms onset, 62,69,87,[134][135][136]138,143,155,161 in six studies within 48 hours, 137,139,141,142,150,165 in one study 140 within 72 hours and in one study 160 within 7 days. Another four studies 9,61,132,144 reported that 'patients were assessed as soon as possible after the event' but did not give a time.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to the timing of patient assessment after the index event, in 10 studies TIA patients were assessed within 24 hours of symptoms onset, 62,69,87,[134][135][136]138,143,155,161 in six studies within 48 hours, 137,139,141,142,150,165 in one study 140 within 72 hours and in one study 160 within 7 days. Another four studies 9,61,132,144 reported that 'patients were assessed as soon as possible after the event' but did not give a time.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
“…One study 128 included a highly selected sample of patients with TIA and carotid stenosis, and three studies 65,141,155 excluded patients with specific conditions [i.e. cardioembolic events or blood coagulation disorders, AF and posterior circulation TIAs, respectively].…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…In 3 cohorts, follow-up data were either incomplete or unavailable beyond 7 days. 19,27,28 18 in CT cohorts). Of those imaged with DWI and CT, 72 (2.2%; 95% CI 1.8 -2.8) and 73 (5.3%; 95% CI 4.2-6.7), respectively, had a recurrent stroke at 7 days.…”
Section: Discussionmentioning
confidence: 97%
“…151 DWI can also assess the degree of brainstem infarction before proceeding with endovascular treatment.…”
Section: Posterior Fossa Strokementioning
confidence: 99%